Agama, Pancasila dan Konflik Sosial di Indonesia - Fauzi, Agus (Lentera Hukum, 2017)
During Reformasi Era, Indonesia has still had serious social issues with reference to social clashes and religious violence. The contestation between majority and minority and the monopoly of interpretation of Pancasila as a state ideology have dominated public sphere which affects on the increase of social clash with various backgrounds. The increase of social clash including religious violence results in the uncertainty whether or not Pancasila as a state ideology is capable of tackling contemporary Indonesian realities. Moreover, Pancasila also needs to tackle religious transnationalism ideology which has spread across the nation and receive positive sympathy from some Indonesians. Based on these realities, this writing aims to examine dimension of divinity and humanism in Pancasila and then propose an ideal concept of the divinity in the framework of Indonesian unity. Keywords: Pancasila, Religious Conflict, Indonesia and Ideology